Anti-browning effect of Rosa roxburghii on apple juice and identification of polyphenol oxidase inhibitors. (15th October 2021) - Yu, Kaibo; Zhou, Lei; Sun, Yuefang; Zeng, Zicong; Chen, Huiwen; Liu, Junping; Zou, Liqiang; Liu, Wei
Graphical abstract: Highlights: Rosa roxburghii (RR) effectively inhibited the browning of apple juice. Ascorbic acid in RR was 1.67 g/100 g and played an important role in anti-browning. Seven phenolic compounds identified by LC-MS/MS were screened as PPO inhibitors. Inhibitors bound to active sites of PPO and influenced the entrance of substrate. Acting forces between inhibitors and PPO were hydrophobic force and hydrogen bond. Abstract: Enzymatic browning control of cloudy fruit juice with natural substances has received much attention for improving its nutritional and commercial value. This study explored the anti-browning potential of Rosa roxburghii in apple juice. The anti-browning effects and mechanisms were evaluated by serial measurements of appearance, browning index, polyphenol oxidase (PPO) activity, UPLC-QE-Orbitrap-MS identification, inhibition kinetics and molecular docking. The results showed that Rosa roxburghii juice (0.25%-1.25% w/w) could effectively inhibit browning and PPO activity of apple juice. Ascorbic acid (1.67 g/100 g) as a reducing agent was a main anti-browning factor. Furthermore, seven phenolic compounds in Rosa roxburghii were screened as PPO inhibitors. Representative phenolic inhibitors induced mixed or competitive inhibition of PPO, mainly driven by hydrophobic forces and hydrogen bonds. This work demonstrates that Rosa roxburghii is a promising natural anti-browning ingredient to control the browning of cloudy apple juice due to abundant ascorbic acid and PPO inhibitors.